ANALEMMA AND THE BEGINNING OF MAGHRIB PRAYER ALTERATION (Correlation Of Analemma’s Position Towards The Beginning Of Maghrib Prayer According To Ephemeris Calculation) - M. Ihtirozun Ni'am; khabib suraya (Fakultas Syari'ah dan Hukum UIN Walisongo, 2021)
Analemmaa is a change of sun’s position which is inconstant when it is observed in certain time and place during a year period. If the change is served as a diagram, it will shape like ‘eight’ number. The beginning of maghrib prayer during a year period is dyanmic at certain time, and it will change due to alteration of sunset. Therefore, this research aimed to understand the correlation between analemma and the alteration of maghrib prayer schedule. The research uses field research method, which collecting the average of observation data of Sun’s position at the certain time and place during a year period by employing qualitative method. The research found that the alteration of the beginning of maghrib prayer is caused by the analemma’s phenomenon. When the gap between the result of analema’s time observed with maghrib schedule is increased, so the beginning of maghrib prayer is delayed. Yet, when the gap between the result of analema’s time observed with maghrib schedule is decreased, so the beginning of maghrib prayer is sooner.